Quality management in the university classroom (Gaceta Técnica, 2018)
This study aimed to address quality management in the university classroom, specifically in the Department of Basic Sciences of the Dean of Civil Engineering of the Universidad Centroccidental Lisandro Alvarado. It was conceived under the modality of qualitative research of ethnographic type with an interpretive character. The research process involved three phases: obtaining information, in which key informants were selected from a group of four (4) teachers and three (3) students in an intentional sampling, interview techniques were applied and participant observation to record and categorize the informants' opinions. In the second phase, the analysis and interpretation of the information was done using the GLATER model, which allowed orientating it from four stages: the first stage assignment of codes and dimensions, second stage of description, third of categorization and fourth stage of interpretation. In the third and final phase the construction of a theoretical approach of the quality management based on the managerial method PDCA, proposed by the researcher, was carried out starting from the analysis of the categories and their properties. As a result of this process, the thematic categories emerged: Integral Training, Availability and Use of School Media, Dynamics of Organizational Learning and Institutional Leadership.
Keywords: university class quality; university management